Perfusion Computed Tomography in the Diagnosis of Colonic Diverticular Disease and its Complications - M. V. Timerbulatov; A. F. Itkulov; D. E. Baikov; A. A. Ibatullin; M. M. Khafizov (Креативная хирургия и онкология, 2023)
Introduction. Colonic diverticular disease (colonic diverticulitis) is considered to be a serious medical and social problem of modern society, marked by a persistent decrease in the quality of life of patients and a steady growth in morbidity with a tendency to increase complications of the underlying disease in the form of inflammatory destructive changes in the intestinal wall.Materials and methods. The study involved 63 patients with colonic diverticulitis, males and females, aged 34 through 79 years. All participants were divided into 3 groups, depending on the damage to the intestinal wall. The first group included 11 patients with intact intestinal wall, the second group included 43 patients with diverticulitis, and the third group — 9 patients with adenocarcinoma of the large intestine.Results and discussion. When performing perfusion computed tomography (PCT) of the intestinal wall, it was found that BF values in acute diverticulitis, compared to the intact intestinal wall, increased on average by 1.7 times, while in malignancies — by 5.3 times. BV values in acute diverticulitis, as compared to the intact intestinal wall, increased by 9.2, and in malignancies — 13.6 times. MRI values in acute diverticulitis, as compared to the intact intestinal wall, increased by 2.5 times, and in malignancies — 3.9 times. PS values in acute diverticulitis, as compared to the intact intestinal wall, increased by 1.7 times, and in malignancies — 3.8 times.Conclusion. Since PCT is able to detect the difference of microcirculation parameters in inflammatory and malignant processes, it can be used in the diagnostic algorithm to determine further treatment strategy.